The Effect of Fraud Hexagon, Good Corporate Governance, and Whistleblowing System in Detecting Fraud in Financial Statements (Empirical Study on Food and Beverage Sub-sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2021-2023 - Wulandari, Dilla Fitri; Fatchan Achyani (Islamic Business and Management Journal, 2025)
Fraud, defined as an intentional act to obtain or lose property through deception or unfair means for personal gain, poses a serious threat to the integrity of financial information and public trust. Although the frequency of cases is lower than asset misappropriation or corruption, financial statement fraud causes the most significant financial losses and has the potential to trigger corporate bankruptcy. This study aims to analyze the influence of Fraud Hexagon, Good Corporate Governance (GCG), and Whistleblowing System in detecting fraud in financial statements. The Fraud Hexagon framework is used to identify the elements that trigger fraud, namely pressure, opportunity, rationalization, capability, arrogance, and collusion. In the context of GCG, this study specifically highlights the role of the Board of Commissioners and the Audit Committee as pillars of internal supervision and control. Meanwhile, the Whistleblowing system is assumed to be an important mechanism in the prevention and early detection of fraudulent practices. The sampling technique used purposive sampling with 87 samples that met the research criteria. The data analysis method used is the classical assumption test and multiple linear regression analysis, with hypothesis testing through the T statistical test, F statistical test, and coefficient of determination. The results of the study indicate that opportunity, capability, and collusion in Fraud Hexagon have a positive effect on financial statement fraud. In addition, the Board of Commissioners also has a positive effect on financial statement fraud. However, pressure, rationalization, and arrogance in Fraud Hexagon, the Audit Committee in GCG, and the Whistleblowing System do not have a significant effect on financial statement fraud.